Spuścizny konserwatorów zbiorów, kierowników i dyrektorów Biblioteki Poznańskiego Towarzystwa Przyjaciół Nauk - Boksa, Michał (Biblioteka Uniwersytecka w Poznaniu, 2011)
Artykuł prezentuje sylwetki konserwatorów zbiorów, kierowników i dyrektorów Biblioteki Poznańskiego Towarzystwa Przyjaciół Nauk (PTPN) oraz to, co po nich pozostało w postaci archiwaliów. Od momentu powstania Biblioteka PTPN gromadziła rękopisy lub całe spuścizny wybitnych osób, w tym kierujących tą placówką. Również inne biblioteki i archiwa zakładowe instytucji, z którymi byli oni związani, włączały do swych zbiorów ich materiały archiwalne. Spuścizny Ludwiki Dobrzyńskiej-Rybickiej i Ryszarda Marciniaka znajdują się zarówno w Bibliotece PTPN, jak i w Polskiej Akademii Nauk Archiwum w Warszawie Oddział w Poznaniu. Znaczna część materiałów archiwalnych Bolesława Erzepkiego trafiła natomiast do Działu Zbiorów Specjalnych Biblioteki Raczyńskich w Poznaniu. Szczątkowe materiały archiwalne można też znaleźć w Archiwum Uniwersytetu im. Adama Mickiewicza w Poznaniu (Ludwika Dobrzyńska-Rybicka) oraz w Archiwum Biblioteki Uniwersyteckiej w Poznaniu (Ludwika Dobrzyńska-Rybicka, Jan Baumgart, Aniela Koehlerówna).

The present article provides a number of profiles of book conservators, heads of the departments of book conservation and directors of the Library of the Poznań Society of the Friends of Sciences (Polish: PTPN) and their legacy remained in the form of available archival material. From its onset, the PTPN Library has been collecting manuscripts and bequests of prominent people that included books and other material, including bequests of those who had been heading the institution. The archival material that belonged to the latter group has been also collected by other libraries and archives with which they were in close contact. The legacy of Ludwika Dobrzyńska-Rybicka and Ryszard Marciniak has been thus split between the PTPN Library and the Library of the Poznań branch of the Polish Academy of Science. The bulk of the archival material bequeathed by Bolesław Erzepki has been located in the Special Collection Division of the Raczyński Municipal Library in Poznań. Residual relevant archival material can be also found in the Archives of the Adam Mickiewicz University in Poznań (L. Dobrzyńska-Rybicka) and in the Archives of Poznań University Library (L. Dobrzyńska-Rybicka, Jan Baumgart, Aniela Koehlerówna).
The legacy of book conservators, heads of departments of conservation and the directors of the Library of the Poznań Society of the Friends of Sciences
Keywords: spuścizna; legacy; biblioteka; library; archiwum; archives